Proform Dynamics in Constituency: Insights from EFL Student Sentences - Sandhi, Muhammad Adithya Huzaifah; Bochari, Siska; Lebagi, Desrin; Hastini, Hastini (e-Journal of Linguistics; Vol 19 No 2 (2025): ejl-JulyDO - 10.24843/e-jl.2025.v19.i02.p01, 2025)
This research investigates the distribution and challenges of proform use among English as a Foreign Language (EFL) learners at Tadulako University, focusing on proform verb phrases (ProVP) and proform prepositional phrases (ProPP). Using a quantitative descriptive approach, data was gathered through tests and questionnaires from samples of 36 fifth-semester students. The analysis reveals that verb phrase proforms, especially those involving tense and aspect, are more challenging for EFL students compared to prepositional phrase proforms. Four factors influencing proform use were identified: first language interference, limited practice in real life, lack of motivation, and ineffective teaching methods. These findings highlight the need for enhanced syntactic training in EFL instruction to improve students’ understanding and application of proforms, supporting more effective sentence construction and overall linguistic competence.